2020
DOI: 10.1002/marc.202000371
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Pulley Effect of Polyrotaxane in Transparent Bulk Polymer for Simultaneous Strengthening and Toughening

Abstract: 2000371 (2 of 7) www.advancedsciencenews.com www.mrc-journal.de Figure 5. a) Frequency dependences of tan δ. b) Continuous relaxation time spectra H(λ) of PMPB-4% and PMPR10-4%. The master curves in (a) are obtained by time-temperature superposition shift with respect to 30 °C. H(λ) in (b) specifies the weight of relaxation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Rheological measurements and tensile strength data showed that post-cross-linking with CMC did not alter the mechanical properties of the collagen hydrogels compared to that with EDC/NHS. These results suggest that the mobility of the threading α-CDs contributes to improving the mechanical properties of the collagen hydrogels because the movable cross-linking points equalize the stress concentration. Therefore, the mechanical properties of the physically cross-linked collagen hydrogels were also improved by post-cross-linking with PRXs, especially CMPRs with a high-molecular-weight polymer axle. It is reported that the molecular weight of the axle polymer strongly affects the tensile strength and elasticity of the PRX-cross-linked hydrogels. , Our results suggest that the molecular weight of the axle polymer in CMPRs is a more important parameter for improving the mechanical properties than the α-CD threading ratios.…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rheological measurements and tensile strength data showed that post-cross-linking with CMC did not alter the mechanical properties of the collagen hydrogels compared to that with EDC/NHS. These results suggest that the mobility of the threading α-CDs contributes to improving the mechanical properties of the collagen hydrogels because the movable cross-linking points equalize the stress concentration. Therefore, the mechanical properties of the physically cross-linked collagen hydrogels were also improved by post-cross-linking with PRXs, especially CMPRs with a high-molecular-weight polymer axle. It is reported that the molecular weight of the axle polymer strongly affects the tensile strength and elasticity of the PRX-cross-linked hydrogels. , Our results suggest that the molecular weight of the axle polymer in CMPRs is a more important parameter for improving the mechanical properties than the α-CD threading ratios.…”
Section: Results and Discussionmentioning
confidence: 94%
“…Therefore, when threading CDs are used as cross-linking points for hydrogels and elastomers, the cross-linking points can move along an axle polymer, similar to pulleys. , When the cross-linked materials are elongated, the mobile cross-linking points equalize the stress concentration. This pulley effect provides excellent stretchability and toughness in cross-linked materials. Therefore, PRX-based cross-linking materials have received increasing attention. , Such a PRX-based cross-linking is also useful for the mechanical reinforcement of hydrogel-based biomaterials, such as collagen, gelatin, and chitosan. For the chemical cross-linking of these hydrogels, aldehyde or carboxy group-modified PRXs are used to allow the reaction with the amino groups in collagen and gelatin hydrogels. These chemically modified PRXs are combined with collagen or gelatin solutions, followed by changing temperature for gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a new peak at δ = 4.04 ppm that is ascribed to the proton of carbamate groups appears on the 1 H NMR spectrum of HPR-S, and there is no obvious signal of CC near 6.0 ppm, implying the complete consumption of methacrylic. 42 As for the new peaks at 2.80, 2.63, and 1.15 ppm, they are attributed to the methine proton signals of propylene glycol groups. Meanwhile, a new strong absorption at 1728 cm −1 is detected on the FTIR spectrum of HPR-S (Figure 1b) as compared to the spectra of PR and HPR, which is ascribed to the signal of the carbonyl groups in carbamate.…”
Section: Resultsmentioning
confidence: 88%
“…Specifically, IEM is first attached to HPR via the classical reaction between −NCO and −OH groups, and then, 2-thioglycerol is added to click the methacrylic groups and graft propylene glycol groups onto HPR for the further reaction of boronic ester (Scheme ). Accordingly, a new peak at δ = 4.04 ppm that is ascribed to the proton of carbamate groups appears on the 1 H NMR spectrum of HPR-S, and there is no obvious signal of CC near 6.0 ppm, implying the complete consumption of methacrylic . As for the new peaks at 2.80, 2.63, and 1.15 ppm, they are attributed to the methine proton signals of propylene glycol groups.…”
Section: Results and Discussionmentioning
confidence: 93%
“…However, it is very difficult to increase the Young’s modulus and maintain toughness when introducing chemical cross-links. A composite with topological network materials is one of solutions for this issue, and tremendous works have been reported. We also prepared CAC/polymer composite materials by bulk polymerization of vinyl monomers with CAC. , These methods can easily prepare the topological polymer networks, such as reversible or movable cross-linking structure, where bulk or solution copolymerization of conventional vinyl monomers with the cyclodextrin (CD) ring monomers takes place. These methods enabled us to find and choose proper monomers for the polymeric composite materials that can be mixed with various fillers to show the desired properties.…”
Section: Introductionmentioning
confidence: 99%